Genes in the field : on-farm conservation of crop diversity - Brush, Stephen B., 1943- (desLibris. Books collection., 2000)
The diversity of crop plants is one of our most important biological resources, and the most important source of crop genes are the fields of peasant farmers in regions where crop domestication and evolution have occurred. Today, however, crop genes are threatened by social and technological change such as human population growth, the use of new agricultural technologies, the development of new varieties, and the commercialization of agriculture. Gene banks have been successful in capturing much of the genetic diversity of crop species, but it is also essential that the environmental systems w.